(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s ((3gHI Gddg YHO GdLHGQ GHf EHQGgje Hf HSGe GdLHdi s)
(3ChdgG (B:s
(3GdHGH GdChd ai eOGhGI hQe GddgGg EPG YQV ddgGg hGdhQe GdLGQ ajfHZi Cf JaUO UGMHgG GdbjaGd hJMd WHjYJg s
(3BNQgG (B:s
(3hjDNP efg ZOhI YTjI eKbGd eY TF ef TGQH GdYSd fGaY Ef TGA Gddg JYGdi s
(3GdLRA GdKGfi GdYedi ef fSNI SGHYIs
(3NRGFfjI fajSI LOkGs
(3hHChdgG agQSJ HCHhGH GdebGdI GdChdis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs